A Hybrid Authenticated Group Key Agreement Protocol in Wireless Sensor Networks. (23rd April 2013) - Li, Yue; Chen, Dehua; Li, Wei; Wang, Gaoli; Smith, Paul
Wireless sensor networks are a modern and advanced technology whose applications are fast developing in recent years. Despite being a fascinating topic with various visions of a more intelligent world, there still exist security issues to be resolved in order to make WSNs fully adoptable. Due to the resource constraints of sensor nodes, it is infeasible to use traditional key establishment techniques that find use in fixed communication systems. In this paper, the design of a new hybrid Authenticated Group Key Agreement (AGKA) protocol is described for WSNs. The AGKA protocol reduces the high cost public-key operations at the sensor side and replaces them with efficient symmetric-key based operations. The proposed AGKA protocol is not only efficient but also meets strong security requirements. In order to demonstrate the protocol is verifiably secure and trustworthy, a formal verification of the AGKA protocol is carried out. Furthermore, several experiments are conducted on MICAz and TelosB platforms in order to evaluate the performance of the proposed protocol. The evaluation results show that the AGKA protocol is well suited for use with resource-constrained sensor nodes.